Strategi Seniman Kaligrafi dalam Mengikuti Lomba Hiasan Mushaf di Kota Palangka Raya - Asep Solikin; Nuraida Rahmi (Jurnal Hadratul Madaniyah, 2017)
Calligraphy or commonly known as khath is one of Islamic art which received considerable attention from the Muslim community, not least the Muslims in the city of Palangkaraya. The calligraphy is used as one of the branches that are contested in Musabaqah Tilawatil Qur'an (MTQ), namely Musabaqah Khattil Qur'an (MKQ). In MKQ divided into three (3) groups: group branches manuscript, ornamentations and decor. The ability of the artists of calligraphy in making adornments at the time of the race would have a different strategy with the aim that the resulting work better and can be categorised as the best. Subject (source data) in this study consists of three (3) artists, calligraphy, calligraphic artist group three are ornamentations with a proven record in the race making adornments. The results showed that: first, the most supportive factor in implementing strategies make decorations Manuscripts at the time of the race, there are two (2) factors: (a) Factors Psychic (Soul), which strengthen the spiritual self to God; (B) Physical elements (Physical), ie prior to the start of the race and to consume nutritious foods and regular breaks; second, the difficulties encountered in making the calligraphy artist ornamentations at the time of the race was the lack of preparation, drafting difficulties paragraph, and problems in the manufacture of trim and motifs. And third, calligraphy artists strategy in making ornamentations at the time of the race, namely by extending the exercise, strengthening the rule of writing (handwriting), regulates the distribution of the time available, it has quality tools, and understand the characteristics of the board of judges.